Red coral (Corallium rubrum) populations and coralligenous characterization within "Regno di Nettuno MPA" (Tyrrhenian Sea, Italy). Issue 1 (1st January 2020) - Ferrigno, F.; Appolloni, L.; Rendina, F.; Donnarumma, L.; Russo, G. F.; Sandulli, R.
Abstract: Red coral is one of the most important species belonging to the coralligenous habitats, being a structuring organism and highly sensitive to human pressure. The presence of red coral populations is historically well documented along the Campania coast (Tyrrhenian Sea), and, due to its high economic value, it has been commercially overharvested since ancient times. Red coral populations along several cliffs on the "Regno di Nettuno" MPA of the Gulf of Naples were investigated using ROV-imaging techniques. Coralligenous habitats were characterized in terms of percent cover and number of morphological groups. Pizzaco site showed the richest and most diverse community. Density of red coral colonies was calculated and compared with morphometric parameters. Results show an inversely correlated trend between colonies density and their size. Finally, fishing pressure was estimated through frequency of lost fishing gears, and S. Angelo site resulted the most stressed one. Anthropic stress plays a key role in the degradation of coralligenous habitats and the dramatic reduction of red coral populations recorded in recent years allows to suspect a more extensive degradation of the entire community. An assessment of the distribution and state of the populations can provide useful information to take measures for a better MPAs management.